Does arsenic pose a health concern after consumption of clay products?. Issue 1 (2nd January 2021) - Demaegdt, Heidi; Waegeneers, Nadia; Cheyns, Karlien; Ruttens, Ann
ABSTRACT: Clay products for oral use form a particular group of food supplements in relation to potential arsenic (As) toxicity, because – certainly in case of pure clay- all arsenic in these supplements is expected to be present in the most toxic inorganic form (Asi ). In terms of risk, the most important questions to answer relate to the bioaccessibility and bioavailability of the inorganic arsenic present, rather than to the As species distribution, which often receives most attention in standard foodstuffs. In the present study, clay products for oral use were bought on the Belgian market and analysed for total arsenic (Astot ), arsenic species (Asi, arsenobetaine, dimethylarsenate and monomethylarsenate)) and bioaccessible arsenic, in order to perform an exposure assessment and risk characterisation. Total As concentrations differed considerably between the samples and ranged from 0.20 to 6.4 mg Astot /kg. Bioaccessibility of Asi, determined via the Unified Barge Method (extraction making use of digestive enzymes) varied between 8% and 51%. The Asi concentration determined via HPLC-ICP-MS after extraction with diluted HNO3 + H2 O2 (as in the CEN method for foodstuffs) was only a poor predictor of the bioaccessible Asi fraction, despite the significant relationship (R 2 = 0.36; p < .05). The risk characterisation did not reveal acute risks related to Asi exposure. However, a potential concern with regard to chronic Asi intake was identified for the general population in 42% of the analysed food supplements, and for sensitive population groups in 67% of the samples, even after taking into account the bioaccessible fraction. The data presented illustrate that consumption of some of these clay products may contribute significantly to dietary Asi intake and that these should not be taken chronically.